Why do firms fail? A new view on bankruptcy from the angle of top management team heterogeneity - Michael Geulen; Andrea Greven; Denise Fischer-Kreer; Malte Brettel (Review of Managerial Science, 2023)
Avoiding bankruptcy is a crucial task for any firm's top management team (TMT), and reasons for the failure to accomplish it have long been studied. While financial metrics can predict near-term bankruptcy, governance characteristics increase precision in the long term. With TMT heterogeneity, we introduce a powerful predictor for the critical time frame in between. Grounded in upper echelons theory, we argue that TMT age heterogeneity increases while heterogeneity in TMT pay and TMT functional backgrounds decreases the bankruptcy probability. We test our hypotheses using a unique dataset of large, public U.S. firms, about half of which filed for bankruptcy between 2001 and 2020. Our results support our research model and show how TMT heterogeneity significantly predicts bankruptcy. We contribute to both bankruptcy and strategic management research by underscoring the importance of TMT heterogeneity as a level of analysis when predicting bankruptcy and add to the ongoing discussion on the impact of TMT pay differences on firm performance. Additionally, we offer valuable insights to practitioners navigating their firms in times of crisis and to regulators shaping the insolvency statutes of the future.
Keywords: G33; M14; G34; M12; 650; Top management team (TMT); Heterogeneity; Corporate governance; Bankruptcy; Firm survival